The Influence of Emotional Intelligence and Communication Competence on Employee Performance in Non-Bank Financial Service Institutions (Cooperatives) by Affective Commitment as a Mediating Variable: A Literature Review on Human Resource Management - Kase, Ratna Eunike; FoEh, John E.H.J. (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The existence of qualified Human Resources in an association is an advantage over other resources in order to accomplish association objectives, to accomplish these objectives human resources do have show aligned performance. Employee performance goes beyond mere task completion but also the capacity to self-regulate, regulate sentiment in interpersonal connections, communication skills to carry out tasks/services to customers and commitment to giving themselves as part of the association and its accomplishments. This article reviews the influence of emotional intelligence, communication skills and affective commitment on employee performance. This research aims to design a hypothesis of the connection among variables so that it be able to be utilized in ensuing studies. The outcomes of the review in this research are: 1) emotional intelligence alters performance; 2) communication skills affect performance; 3) affective commitment alters performance and 4) affective commitment mediates the connection among emotional intelligence and employee performance.